1999
DOI: 10.1002/jlb.66.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of leukocyte adherence and migration by glycosylphosphatidyl-inositol-anchored proteins

Abstract: Leukocyte extravasation is essential for subsequent inflammation and the immune response. Extravasation can be divided into at least three steps; rolling, firm adhesion, and transendothelial migration. Although the mechanisms involved in the first two steps have been fairly well documented, the last step is complex and largely remains to be clarified. This review focuses on the possible role of GPI-anchored proteins on leukocytes in the regulation of their transendothelial migration. In addition to regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…It has previously been shown that the GPI-80 is a possible regulatory molecule of cell adhesion and migration. [18][19][20] GPI-80 protein has a high sequence homology with Vanin-1, 21) which is expressed on perivascular thymic stromal cells and is involved in thymus homing in mice. 22) There is about 60% molecular homology between GPI-80 and Vanin-1, and these two molecules share a similar function in the sense that both may be involved in the regulation of leukocyte trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the GPI-80 is a possible regulatory molecule of cell adhesion and migration. [18][19][20] GPI-80 protein has a high sequence homology with Vanin-1, 21) which is expressed on perivascular thymic stromal cells and is involved in thymus homing in mice. 22) There is about 60% molecular homology between GPI-80 and Vanin-1, and these two molecules share a similar function in the sense that both may be involved in the regulation of leukocyte trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Structural characterization of uPAR has shown that it is a glycosylated single polypeptide linked to the plasma membrane by a GPI anchor (37). Several GPI-anchored proteins are known to regulate cellular activation, adhesion, and migration (38), even though GPI anchors only penetrate the outer leaflet of the plasma membrane and thus have no direct access to cytoplasmic signaling intermediates. The ability of uPAR to complex with membrane-spanning proteins has suggested that uPAR can initiate leukocyte activation by appropriating the signaling mechanisms of a partner protein such as CR3, in effect using it as a signal transduction device.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53][54] Integrins mediate cell adhesion, migration, phagocytosis, and virtually all PMN functions. To accomplish their roles, integrins must act not only as individual receptors, but also as components of supramolecular complexes at the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%